The proteolytic processing of amelogenin by enamel matrix metalloproteinase (MMP-20) is controlled by mineral ions - Khan, Feroz (2013)
BACKGROUND: Enamel synthesis is a highly dynamic process characterized by simultaneity of matrix secretion, assembly and processing during apatite mineralization. MMP-20 is the first protease to hydrolyze amelogenin, resulting in specific cleavage products that self-assemble into nanostructures at specific mineral compositions and pH. In this investigation, enzyme kinetics of MMP-20 proteolysis of recombinant full-length human amelogenin (rH174) under different mineral compositions is elucidated. METHODS: Recombinant amelogenin was cleaved by MMP-20 under various physicochemical conditions and the products were analyzed by SDS-PAGE and MALDI-TOF MS. RESULTS: It was observed that mineral ions largely affect cleavage pattern, and enzyme kinetics of rH174 hydrolysis. Out of the five selected mineral ion compositions, MMP-20 was most efficient at high calcium concentration, whereas it was slowest at high phosphate, and at high calcium and phosphate concentrations. In most of the compositions, N- and C-termini were cleaved rapidly at several places but the central region of amelogenin was protected up to some extent in solutions with high calcium and phosphate contents. CONCLUSION: These in vitro studies showed that the chemistry of the protein solutions can significantly alter the processing of amelogenin by MMP-20, which may have significant effects in vivo matrix assembly and subsequent calcium phosphate mineralization. GENERAL SIGNIFICANCE: This study elaborates the possibilities of the processing of the organic matrix into mineralized tissue during enamel development.